2011
DOI: 10.1088/0031-9155/56/3/008
|View full text |Cite
|
Sign up to set email alerts
|

In vivomeasurement of lead in the bones of smelter workers using the four-element ‘clover-leaf’ geometry detector system

Abstract: A total of 497 smelter employees from New Brunswick participated in a bone lead survey conducted by McMaster University in 2008 to examine the efficiency of lead exposure control programmes and a four-element 'clover-leaf' geometry detector system. Nearly 42% of the subjects had participated in both the previous surveys performed in 1994 and 1999. After developing the clover-leaf geometry system in 2006, the reliability of the system based on examining the consistency of four detectors and improving the minimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…The group of study consisted of the smelter employees from New Brunswick who have participated in longitudinal studies performed in 1994, 1999, and 2008. [8][9][10] For the 211 employees who were common between the three groups, the respective mean (SD, Standard Deviation) of tibia and calcaneus was 27.62 (18.57) and 41.70 (29.26) mg Pb per g bone mineral in 2008; the ones in 1999 were found to be 37.84 (29.68) and 76.07 (49.47), and nally the bone lead values in 1994 were found to be 37.33 (29.04) and 61.25 (54.74) mg Pb per g bone mineral respectively. The mean change in CBLI between the two lead measurements in 2008 À 1999 and 1999 À 1994 were 151.7 and 110.7 mg year per dl respectively.…”
Section: Study Groupsmentioning
confidence: 99%
“…The group of study consisted of the smelter employees from New Brunswick who have participated in longitudinal studies performed in 1994, 1999, and 2008. [8][9][10] For the 211 employees who were common between the three groups, the respective mean (SD, Standard Deviation) of tibia and calcaneus was 27.62 (18.57) and 41.70 (29.26) mg Pb per g bone mineral in 2008; the ones in 1999 were found to be 37.84 (29.68) and 76.07 (49.47), and nally the bone lead values in 1994 were found to be 37.33 (29.04) and 61.25 (54.74) mg Pb per g bone mineral respectively. The mean change in CBLI between the two lead measurements in 2008 À 1999 and 1999 À 1994 were 151.7 and 110.7 mg year per dl respectively.…”
Section: Study Groupsmentioning
confidence: 99%
“…When compared with occupationally exposed subjects, levels from a survey conducted at a lead smelter in New Brunswick in 2008, and reported in 2011, by Behinaein et al on 497 individuals, tibia lead levels ranged from 0 to 100.2 µg Pb/g bone mineral. The Paget's femur levels are thus within those found occupationally.…”
Section: Discussion and Future Workmentioning
confidence: 91%
“…Bone and Tooth Pb Measurements. The development of noninvasive XRF techniques for measuring Pb concentrations in bone has enabled the exploration of bone Pb as a biomarker of Pb exposure in children and in adults (Behinaein et al 2011;Chettle et al 2003;Hu et al 2007;Ji et al 2014;Nie et al 2011b;Specht et al 2016;Todd et al 2000). Pb in bone is considered a biomarker of cumulative exposure to Pb because Pb accumulates in bone over the lifetime and most of the Pb body burden resides in bone.…”
Section: Biomarkers Of Exposurementioning
confidence: 99%
“…One study reported a correlation of 0.65 between bone Pb measurements made with a portable L-shell device and a K-shell method (Nie et al 2011a). In general, recent advances in K-shell technology have yielded higher sensitivities (approximately 3 µg/g tibia mineral; Behinaein et al 2011) than L-shell technology (approximately 8 µg/g tibia bone mineral; Nie et al 2011a). Precision of K-shell XRF bone Pb measurements have been extensively discussed (Aro et al 2000;Behinaein et al 2014;Todd et al 2000Todd et al , 2001Todd et al , 2002.…”
Section: Biomarkers Of Exposurementioning
confidence: 99%